CHANGING NOTATION INFIX BENEFIT FROM BECOMING POSTFIX STACK - Edwin Hutabarat; Ir. Irwan Bastian (Jurnal Sistem Informasi, 1996)
Stack is used regularly to indicate a data collection process, where the process wasgoing according to the order. So something specific process should be postponed untilanother process is complete.This compilation engine will be easier to handle expressions in the form of a positivenotation.